The Pillars of the IJTMB—Looking More Closely at the Practice Section - Baskwill, Amanda (International Journal of Therapeutic Massage & Bodywork, 2024)
This editorial continues the exploration of the three pillars of the International Journal of Therapeutic Massage and Bodywork. We discuss opportunities in TMB practice to share experiences and learnings with the IJTMB community. Several exemplars of manuscripts published in the Practice Sections are shared for inspiration.